Supporting women's empowerment and climate resilience through socio-technical innovation bundles - Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2023)
Ranjitha Puskur, lead of the EMPOWER work package, explains how they support women’s empowerment and climate resilience through socio-technical innovation bundles , the importance of climate-smart agricultural technologies and the need to provide women with access to these technologies, along with access to finance and extension services, among others. The fireside conversation with Dr Mahesh Chander, principal scientist at ICAR-Indian Veterinary Research Institute, showcases a shift in technology transfer in agrifood systems. While men have traditionally dominated the discussions with researchers and extension agents, women in South Asia now seek comprehensive and inclusive solutions that cater to their specific preferences and needs.